Desenvolvimento inicial de maracujazeiros (Passiflora edulis f. flavicarpa, P. edulis f. edulis e P. alata) enxertados sobre Passiflora cincinnata - Zucareli, Valdir; Ono, Elizabeth Orika [UNESP]; Fernandes Boaro, Carmen Silvia [UNESP]; Brambilla, Wilian Polaco [UNESP] (Univ Estadual Londrina, 2014)
The present work aimed to evaluate the initial growth and leaf mineral levels in passion fruit trees (Passiflora edulis f. flavicarpa Deg., P. edulis f. edulis Sims. and P. alata Dryander) grafted onto Passiflora cincinnata. To obtain seedlings, seeds were sown in plastic bags (500 mL) and hypocotyl grafting was performed when seedlings reached the stage of two fully expanded leaves. Fifteen days after grafting, plants were transplanted to 10L pots filled with previously limed and fertilized soil. Each pot contained two plants and corresponded to one plot. For each commercial species studied as rootstock, experimental design was completely randomized, in 3x5 (plant type x time of harvest) factorial arrangement, with four replicates of two plants per plot and five destructive harvests. Plant types were ungrafted P. cincinnata, ungrafted commercial passion fruit tree and commercial passion fruit tree grafted onto P. cincinnata. The first harvest was performed at 15 days after transplanting and the remaining ones at 14-day intervals (60, 74, 88, 102 and 116 DAS). At each harvest, the number of leaves per plant was counted, and leaf area, stem length, and stem, root, leaf and total dry matter were estimated. At the last harvest, the mineral composition (macro and micronutrients) of plants was analyzed. In general, it was observed that grafting onto P. cincinnata did not interfere negatively with the initial development and mineral levels of commercial passion fruit trees, and this interference varied according to the used canopy.

O presente trabalho teve como objetivo avaliar o desenvolvimento inicial e os teores foliares de minerais em plantas de maracujazeiros (Passiflora edulis f. flavicarpa Deg., P. edulis f. edulis Sims. e P. alata Dryander) enxertadas sobre Passiflora cincinnata. Para a obtenção das mudas, as sementes foram semeadas em sacolas plásticas (500 mL) e quando as plântulas atingiram o estádio de duas folhas expandidas foi realizada a enxertia hipocotiledonar. Quinze dias após a enxertia foi realizado transplantio para vasos de 10 litros preenchidos com terra previamente corrigida e adubada, sendo utilizadas duas plantas por vaso e cada um correspondendo a uma parcela. Para cada espécie comercial estudada como enxerto foi utilizado delineamento experimental inteiramente casualizado em esquema fatorial 3 x 5 (tipo de planta x época de coleta) com quatro repetições de duas plantas por parcela e cinco coletas destrutivas. Como tipo de planta foi considerado P. cincinnata não enxertada, maracujá comercial não enxertado e maracujá comercial enxertado sobre P. cincinnata. A primeira coleta foi realizada 15 dias após o transplantio e as demais em intervalos de 14 dias (60, 74, 88, 102 e 116 DAS). Em cada coleta foi contado o número de folhas por planta e realizadas medidas de área foliar, comprimento de caule, massa da matéria seca total, caule, raiz e folhas. Na última coleta foi realizada a análise da composição mineral das plantas (macro e micronutrientes). De forma geral, foi observado que a enxertia sobre a espécie P. cincinnata não interferiu de maneira prejudicial no desenvolvimento inicial e nos teores de minerais das plantas de maracujazeiros comerciais e que essa interferência variou conforme a copa utilizada.
Initial development of passion fruit trees (Passiflora edulis f. flavicarpa, P. edulis f. edulis and P. alata) grafted onto Passiflora cincinnata
Keywords: Grafting; Passion fruit; Propagation; Enxertia; Maracujá; Propagação